2012
DOI: 10.1371/journal.pone.0034515
|View full text |Cite
|
Sign up to set email alerts
|

Network Analysis of Epidermal Growth Factor Signaling Using Integrated Genomic, Proteomic and Phosphorylation Data

Abstract: To understand how integration of multiple data types can help decipher cellular responses at the systems level, we analyzed the mitogenic response of human mammary epithelial cells to epidermal growth factor (EGF) using whole genome microarrays, mass spectrometry-based proteomics and large-scale western blots with over 1000 antibodies. A time course analysis revealed significant differences in the expression of 3172 genes and 596 proteins, including protein phosphorylation changes measured by western blot. Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(68 citation statements)
references
References 54 publications
5
63
0
Order By: Relevance
“…Thus, inhibiting normal autocrine signaling in HMECs by blocking EGFR with the monoclonal antibody 225 mAb (42) should show a reciprocal effect to adding exogenous EGF. Because of the relatively low sensitivity of global proteomics measurements in detecting EGF-induced protein changes (34), we used transcriptome assays (microarray and RNA-Seq) as a first-pass surrogate for relative protein abundance. To determine which EGF-induced changes resulted from activation of the MAPK pathway, we identified genes whose expression was modulated by the addition of the MEK inhibitor U0126.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, inhibiting normal autocrine signaling in HMECs by blocking EGFR with the monoclonal antibody 225 mAb (42) should show a reciprocal effect to adding exogenous EGF. Because of the relatively low sensitivity of global proteomics measurements in detecting EGF-induced protein changes (34), we used transcriptome assays (microarray and RNA-Seq) as a first-pass surrogate for relative protein abundance. To determine which EGF-induced changes resulted from activation of the MAPK pathway, we identified genes whose expression was modulated by the addition of the MEK inhibitor U0126.…”
Section: Resultsmentioning
confidence: 99%
“…Bioinformatics is also faced with the challenge of how to best integrate multiple data types. Transcriptome data provides a readout for gene regulation at the mRNA level, however, correlation of mRNA with its associated protein expression can be relatively low [7,8]. Proteome data provides a complementary picture of protein expression levels; but current proteomics technologies provide only limited coverage of the proteome.…”
Section: Introductionmentioning
confidence: 99%
“…Proteome data provides a complementary picture of protein expression levels; but current proteomics technologies provide only limited coverage of the proteome. Despite these limitations, integration of these discrete data types has merit and can provide significantly improved coverage of signaling networks [7]. Our group and others have developed advanced bioinformatics capabilities to facilitate the integration of diverse data types [7,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…A number of transcriptome and proteome data integration studies have already been reported e.g. in cell lines [66][67][68], plants [69], and mammal models [6,[70][71][72][73]. The correlation between mRNA and protein abundances in the cell has been reported to be notoriously poor.…”
mentioning
confidence: 99%